ELECTRICITY GENERATION FROM ARTIFICIALWIND GENERATED BY THE MOVING VEHICLES (International Journal of Food and Nutritional Sciences, 2022)
The improvements in renewable energysources are increasing rapidly for controlling thepollution in the atmosphere caused by non-renewableenergy sources.